Investigation of STEM Supported Engineering and Design Experiences of Students Participating in Design and Innovation Workshop in the Context of Situational Interest Theory - Ibrahim Benek; Ismail Donmez; Sahin Idil (Journal of Education in Science, Environment and Health)
This study aims to examine the engineering and design-supported STEM (Science, Technology, Engineering, and Mathematics) experiences of students who participated in the "Design and Innovation Workshop" organized at the Science and Art Center (SAC) during the semester break. The experiences and perceptions of 17 students (10 males and 7 females) were analyzed in depth in this study, which was conducted using a phenomenology design from qualitative research methods. Semi-structured interview form, student diaries, field notes and STEM product drawing form were used as data collection tools. The research findings showed that students' participation in design and engineering-based STEM activities enhanced their problem-solving skills, creativity and teamwork. The theory accompanying the research suggests that these activities increase students' interest and motivation in STEM disciplines. The research results suggest that design and innovation workshops can positively influence students' attitudes and skills towards STEM fields.